Impacts of local environment and land use/cover on spatial-temporal patterns of α and β fish diversity in the Anning River, China - Ruihang Zhou; Pengcheng Lin; Zhijun Xia; Tao Chang; Huijun Ru; Yunfeng Li; Baoshan Ma (Global Ecology and Conservation, 2025)
Biodiversity is a fundamental element of ecosystem function and balance, contributing significantly to resilience against climate change and environmental stressors. Despite extensive studies on species diversity, in-depth exploration into the functional differences among species remains insufficient. Such differences are crucial for revealing the processes involved in community assembly. To examine the spatial and temporal patterns and the driving factors of fish species and functional diversity, surveys were conducted at 28 sampling sites along the Anning River in November 2020 and April 2021. The findings indicated that 60 fish species were collected in total. Spatially, α diversity (richness) followed a hump-shaped pattern, while β diversity displayed a U-shaped distribution along the altitude gradient. Temporally, α diversity (richness) was higher in April compared to November, whereas β diversity and turnover were lower in April. Variance partitioning analysis showed that two types of environmental factors had a greater influence on α diversity compared to β diversity, and a stronger impact on species diversity than on functional diversity. Additionally, local habitat conditions more significantly affected α diversity, while land use/cover had a stronger effect on β diversity. This research advances understanding of the ecological processes that drive fish diversity in freshwater systems and provides essential insights for future conservation and management initiatives.